Analisis Peran Gen AI dalam Penetration Testing: Studi Kasus Mesin VulnHub Menggunakan GPT-4.1 dan Kali Linux - Ho, Jason; Ramadhan, Dimas Fajar; Aluska, Alfa Renaldo (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Along with the increasing threat of cybercrime, which is predicted to cause losses of up to US10.5 trillion by 2025 , penetration testing (pentest) has become a crucial strategy for identifying security vulnerabilities. However, the manual pentest process is often time-consuming. This research aims to analyze the role, effectiveness, and challenges of Generative AI (GenAI), specifically GPT-4.1, in accelerating and optimizing the penetration testing process. This research method uses a qualitative approach with a case study on the